Antifungal agents as tools in experimental mycology - Betina, V (Folia microbiologica, 1985)
Both natural and synthetic substances are conveniently used for studying metabolism, genetic aspects, morphogenesis of cell structures, life cycle and differentiation of fungi.
Keywords: houby; morfogeneze; buněčná diferenciace; Cell Differentiation; Antifungal Agents; Fungi; Morphogenesis; antifungální látky